Robotics: Science and Systems III 2007
DOI: 10.15607/rss.2007.iii.014
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Localisation and Mapping in Dynamic Environments (SLAMIDE) with Reversible Data Associa

Abstract: The conventional technique for dealing with dynamic objects in SLAM is to detect them and then either treat them as outliers [20][1] or track them separately using traditional multi-target tracking [18]. We propose a technique that combines the least-squares formulation of SLAM and sliding window optimisation together with generalised expectation maximisation, to incorporate both dynamic and stationary objects directly into SLAM estimation. The sliding window allows us to postpone the commitment of model selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 21 publications
(21 reference statements)
1
47
0
1
Order By: Relevance
“…In feature based SLAM, coordinates in the global frame are explicitly represented as landmarks, m, which are part of the state vector. The standard assumption is that the landmarks are stationary but dynamic objects can naturally be included in the state vector (Bibby and Reid, 2007). Assume that measurements arrive in the same rate as the dynamic model.…”
Section: Ekf-slammentioning
confidence: 99%
“…In feature based SLAM, coordinates in the global frame are explicitly represented as landmarks, m, which are part of the state vector. The standard assumption is that the landmarks are stationary but dynamic objects can naturally be included in the state vector (Bibby and Reid, 2007). Assume that measurements arrive in the same rate as the dynamic model.…”
Section: Ekf-slammentioning
confidence: 99%
“…Alternatively moving objects are detected and tracked separately using multi-target tracking techniques [6]. Another recent approach tries to classify landmarks as moving or stationary, and incorporates reversible data association within a sliding window of recent observations, to allow moving objects to be included into the Simultaneous Localization and Mapping (SLAM) estimate [7]. In general, while these approaches mitigate some problems of classical SLAM algorithms, they cannot handle long-term changes to the structure of an environment.…”
Section: Related Workmentioning
confidence: 99%
“…While a globally consistent solution to the localization problem must necessarily also perform mapping (Thrun, 2003), many applications do not require or benefit from a globally consistent map. Locally consistent approaches such as fixed-time-window SLAM (Bibby and Reid, 2007) and visual odometry (Nistér et al, 2004;Agrawal and Konolige, 2007) have shown great success in applications such as goal-directed navigation and localization in dynamic environments.…”
Section: Fast Rotational Visual Odometrymentioning
confidence: 99%